2023
DOI: 10.3389/ijph.2023.1605648
|View full text |Cite
|
Sign up to set email alerts
|

Associations of the Triglyceride and Glucose Index With Hypertension Stages, Phenotypes, and Their Progressions Among Middle-Aged and Older Chinese

Abstract: Objectives: To assess the associations of the triglyceride and glucose (TyG) index with hypertension stages, phenotypes, and their progressions.Methods: The data originated from the China Health and Retirement Longitudinal Study. Multinomial logistic regression investigated the associations of the TyG index with hypertension stages (stage 1, stage 2), phenotypes (isolated systolic hypertension [ISH], isolated diastolic hypertension [IDH], systolic diastolic hypertension [SDH]), their progressions.Results: Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Previous studies have con rmed the TyG index was associated with hypertension [10-13, 15, 29, 30] [31]. Another large population-based study (n = 47,808) also reported TyG index signi cantly associated with hypertension in either total subjects or subjects separated into men and women [13].…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Previous studies have con rmed the TyG index was associated with hypertension [10-13, 15, 29, 30] [31]. Another large population-based study (n = 47,808) also reported TyG index signi cantly associated with hypertension in either total subjects or subjects separated into men and women [13].…”
Section: Discussionmentioning
confidence: 75%
“…Our study observed that females had signi cant higher risk of hypertension in the "moderate increasing" and "high stable" TyG index trajectories than males. Another study based on middle-aged and older Chinese, using China Health and Retirement Longitudinal Study (CHARLS) data, also found that higher TyG index was signi cantly associated with stage 2 hypertension in females, but not in males [31]. However, previous study from Spanish cohort has reported that the top quintile of TyG index in men had two times more likely to develop hypertension than those in the bottom quintile, and the effect was attenuated in women [36].…”
Section: Discussionmentioning
confidence: 94%
“…The TyG index, which is produced from fasting triglyceride and glucose levels, has been widely used as a key marker of IR, particularly peripheral and hepatic IR. Several epidemiological studies have reported a significant association of higher TyG scores with the risk of type 2 diabetes mellitus (T2DM) ( 31 , 32 ), prediabetes ( 33 ), hypertension ( 34 ), cardiovascular disease (CVD) ( 35 ), coronary artery calcification ( 36 ), and polycystic ovary syndrome (PCOS) ( 37 ), which can be explained by IR. Mechanically, IR may explain the link between the TyG index and lean NAFLD.…”
Section: Discussionmentioning
confidence: 99%